2000
DOI: 10.1046/j.1365-2672.2000.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

The lactoperoxidase system: the influence of iodide and the chemical and antimicrobial stability over the period of about 18 months

Abstract: The lactoperoxidase (LP) system is a natural antimicrobial system, the use of which has been suggested as a preservative in foods and pharmaceuticals. The effect of adding iodide to the LP system, the chemical stability and the change in antimicrobial effectiveness during storage was studied. Addition of iodide with thiocyanate increased the fungicidal and bactericidal effect against Candida albicans, Escherichia coli and Staphylococcus aureus. Pseudomonas aeruginosa showed the same inhibition in the LP system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 10 publications
3
77
1
Order By: Relevance
“…Bosch et al demonstrated that LPO at a concentration of 387 nM in an LPO system similar to the one used here was sufficient to kill 1,000,000 CFU of C. albicans, E. coli, Staphylococcus aureus, and P. aeruginosa when exposed to the LPO system in solution for at least two hours [27]. We found that a slightly lower concentration of LPO (323 nM) was sufficient to inhibit, but not kill, the fungi R. solani and F. graminearum, and a much lower concentration (20 nM) was sufficient to completely kill the oomycete P. ultimum.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Bosch et al demonstrated that LPO at a concentration of 387 nM in an LPO system similar to the one used here was sufficient to kill 1,000,000 CFU of C. albicans, E. coli, Staphylococcus aureus, and P. aeruginosa when exposed to the LPO system in solution for at least two hours [27]. We found that a slightly lower concentration of LPO (323 nM) was sufficient to inhibit, but not kill, the fungi R. solani and F. graminearum, and a much lower concentration (20 nM) was sufficient to completely kill the oomycete P. ultimum.…”
Section: Discussionmentioning
confidence: 83%
“…We found that a slightly lower concentration of LPO (323 nM) was sufficient to inhibit, but not kill, the fungi R. solani and F. graminearum, and a much lower concentration (20 nM) was sufficient to completely kill the oomycete P. ultimum. Although the LPO concentrations that were used in the Bosch et al study were relatively similar to the highest LPO concentration that was included in this study, the assay conditions were very different [27]. The majority of studies on the antimicrobial activity of the LPO system conducted to date, including the Bosch et al study, have involved bacteria and yeasts that were exposed to a non-stabilized LPO system in a liquid suspension [27].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other investigations demonstrated 1) that lactoperoxidase activity was not modified by coating onto titanium, 2) that lactoperoxidase incorporated in oral gel maintained its activity for at least one year, and 3) that the substrate exhaust (namely hydrogen peroxide and iodide) was the true limiting factor (Bosch et al, 2000;Ahariz et al, 2000). Previous investigations indicated an antibacterial effect on Gram-positive and Gram-negative bacteria, which suggests a non-specific inhibitory effect of hypoiodite on microbial metabolism and growth (Courtois et al, 1995).…”
Section: New Strategies Based On Research In Exocrine Biologymentioning
confidence: 99%